The Ma_Miss instrument performance, II: Band parameters of rocks powders spectra by Martian VNIR spectrometer. (November 2015) - De Angelis, Simone; De Sanctis, Maria Cristina; Ammannito, Eleonora; Carli, Cristian; Di Iorio, Tatiana; Altieri, Francesca
Abstract: The Ma_Miss instrument (Mars Multispectral Imager for Subsurface Studies, Coradini et al. (2001)) is a Visible and Near Infrared miniaturized spectrometer that will observe the Martian subsurface in the 0.4–2.2 μm spectral range. The instrument will be entirely hosted within the Drill of the ExoMars-2018 Pasteur Rover: it will allow analyzing the borehole wall excavated by the Drill, at different depths, down to 2 m. The aim will be to investigate and characterize the mineralogy and stratigraphy of the shallow Martian subsurface. A series of spectroscopic measurements have been performed in order to characterize the spectral performances of the laboratory model of the instrument (breadboard). A set of six samples have been analyzed. Each sample (four volcanic rocks, a micritic limestone and a calcite) has been reduced in particulate form, ground, sieved and divided into nine different grain sizes in the range d <0.02÷0.8 mm. Spectroscopic measurements have been performed on all samples using two distinct experimental setup: (a) the Ma_Miss breadboard, and (b) the Spectro-Goniometer setup, both in use in the laboratory at INAF – IAPS. In a previous paper spectral parameters such as the continuum slope and the reflectance level of the spectra have been discussed (De Angelis et al., 2014). In this work we focus our discussion on absorption band parameters (position, depth, area, band slope and asymmetry). We analyzed/investigated the absorption features at 1 μm for the volcanic samples and at 1.4, 1.9 and 2.2 μm for the two carbonate samples. Band parameters have been retrieved from spectra measured with both experimental setup and then compared. The comparison shows that band parameters are mutually consistent: band centers (for carbonate samples) are similar within few percent, and band depth and area values (for carbonates) show consistent trends vs. grain size (decreasing towards coarser grains) for most of samples. Highlights: Most band parameters vs. grain size trends are consistent for the two instruments. VNIR spectroscopy measures performed with ExoMars/Ma_Miss breadboard and FieldSpec. Breadboard setup: high spatial resolution (120 μm) and 0.35–2.5 μm spectral range. Six particulate rocks analyzed in nine grain-sizes, from d <0.02 mm to 0.50–0.80 mm. Spectral parameters (band area, depth, center, slope and asymmetry) analyzed.